The effects of increases in carbon prices in Malta: A study using MEDSEA-NRG - Noel Rapa (Central Bank of Malta, 2024)
This paper documents the extension of MEDSEA, a small open economy DSGE model for Malta, with a detailed energy sector. The model contains relatively rich fiscal and energy blocks allowing the model to simulate the transitional costs related to the economy's decarbonisation, together with the effects of the possible recycling of carbon tax revenues. Temporary simulations show that taxing fossil-based energy leads to a prolonged drop in economic activity, together with a relatively short-lived increase in consumer price inflation. Energy taxes are found to have asymmetric effects on households, with poorer households being more heavily hit by higher energy prices. Policy experiments show that a decarbonisation policy based solely on increases in carbon taxes will lead to a substantial drop in economic activity with some pressures on inflation, with below target increases in green energy take-up and below target cuts in Green House Gasses. Effects are also expected to be asymmetric with poorer households projected to cut their consumption by more than average. The distributional effects of decarbonisation policies are well addressed by both symmetric and targeted increases in lump-sum transfers. However, recycling carbon revenues by increasing subsidies to green capital is most efficient in reducing the economic costs associated with increases in carbon prices and in attaining environmental targets in terms of reduced emissions and increased take-up of renewable energy.
Keywords: C54; E62; H23; Q43; 330; Climate change; carbon taxation; fiscal policy; DSGE models